Management Whitepaper: Sharing is Caring An Exploration of Motivations for Social Sharing and Locational Social Media Usage among Sport Fans - Galen Clavio; Evan Frederick (Journal of Applied Sports Management, 2014)
Research Problem The purpose of this paper is to examine the phenomenon of social sharing via locational social media in sport and to examine what motivations sport fans have for sharing of information in a public manner via these social media. Social sharing and locational social media are an area of growing importance to both sport organizations and their fans due to the interactive nature of the involved media and the ability of teams to simultaneously foster fan community initiatives as well as monetary incentives. This research contains information that reveals reasons why fans of college athletics share sport event-related information via social media, the likelihood of fans sharing certain types of information via social media, and the types of incentives that might increase fan participation in social sharing via social media. This research also evaluates the factors that underlie social sharing by college sport fans, discovering that these fans share sport event-related information for purposes of event/team promotion and fanship, rather than personal monetary gain. This article would be useful to any sport marketing or communication department personnel who are interested in increasing their organization’s online community initiatives among fans, providing key insights into what is a little-understood dimension of social media and sport.